Validity of a local positioning system during outdoor and indoor conditions for team sports - Alt, P. S.; Baumgart, C.; Ueberschär, O.; Freiwald, J.; Hoppe, M. W. (Sensors, 2020)
This study aimed to compare the validity of a local positioning system (LPS) during outdoor and indoor conditions for team sports. The impact of different filtering techniques was also investigated. Five male team sport athletes (age: 27 ± 2 years; maximum oxygen uptake: 48.4 ± 5.1 mL/min/kg) performed 10 trials on a team sport-specific circuit on an artificial turf and in a sports hall. During the circuit, athletes wore two devices of a recent 20-Hz LPS. From the reported raw and differently filtered velocity data, distances covered during different walking, jogging, and sprinting sections within the circuit were computed for which the circuit was equipped with double-light timing gates as criterion measures. The validity was determined by comparing the known and measured distances via the relative typical error of estimate (TEE). The LPS validity for measuring distances covered was good to moderate during both environments (TEE: 0.9-7.1%), whereby the outdoor validity (TEE: 0.9-6.4%) was superior than indoor validity (TEE: 1.2-7.1%). During both environments, validity outcomes of an unknown manufacturer filter were superior (TEE: 0.9-6.2%) compared to those of a standard Butterworth filter (TEE: 0.9-6.4%) and to unprocessed raw data (TEE: 1.0-7.1%). Our findings show that the evaluated LPS can be considered as a good to moderately valid tracking technology to assess running-based movement patterns in team sports during outdoor and indoor conditions. However, outdoor was superior to indoor validity, and also impacted by the applied filtering technique. Our outcomes should be considered for practical purposes like match and training analyses in team sport environments.